Effect of Hopelessness on Labor Absorption: An Analysis from Organizational Psychology - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
This study analyzes the relationship between Hopelessness and Absorption in the work environment, with the purpose of evaluating how the perception of lack of control and negative expectations can affect the immersion of employees in their tasks. The research is based on theoretical models on work engagement, emotional regulation, and cognition at work, considering that a high level of hopelessness can decrease employees’ ability to stay focused on their duties. It is hypothesized that employees with higher levels of hopelessness experience less absorption at work, suggesting that emotional stability and the perception of control over the organizational environment may be determinants in attentional focus and task involvement. To evaluate this relationship, a quantitative design based on simple linear regression was used. The estimated econometric model shows that the coefficient of the variable Hopelessness is negative and significant (p<0.05p < 0.05), indicating that an increase in hopelessness is associated with a decrease in labor absorption. In addition, the F-statistic test suggests that the model is globally significant, allowing the results to be interpreted with confidence. The findings suggest that hopelessness may be a factor that negatively influences the level of employee absorption, which has implications for talent management and the design of organizational strategies aimed at strengthening work commitment. It is recommended that future research incorporate moderating variables such as organizational resilience and emotional regulation, in order to better understand the mechanisms underlying this relationship.